Nuclear DNA markers for identification of Beluga and Sterlet sturgeons and their interspecific Bester hybrid - Miloš Havelka; Takafumi Fujimoto; Seishi Hagihara; Shinji Adachi; Katsutoshi Arai (Scientific Reports, 2017)
Abstract Sturgeons (Acipenseriformes) are among the most endangered species in the world due to fragmentation and destruction of their natural habitats and to overexploitation, mainly for highly priced caviar. This has led to the development of sturgeon culture, originally for reintroduction, but more recently for caviar production. In both cases, accurate species identification is essential. We report a new tool for accurate identification of Huso huso and Acipenser ruthenus based on nuclear DNA markers. We employed ddRAD sequencing to identify species-specific nucleotide variants, which served as specific binding sites for diagnostic primers. The primers allowed identification of Huso huso and Acipenser ruthenus as well as their discrimination from A. baerii, A. schrenckii, A. gueldenstaedtii, A. stellatus, A. persicus, A. mikadoi, A. transmontanus, and H. dauricus and identification of A. ruthenus and H. huso hybrids with these species, except hybrid between A. ruthenus and A. stellatus. The species-specific primers also allowed identification of bester (H. huso × A. ruthenus), the most commercially exploited sturgeon hybrid. The tool, based on simple PCR and gel electrophoresis, is rapid, inexpensive, and reproducible. It will contribute to conservation of remaining wild populations of A. ruthenus and H. huso, as well as to traceability of their products.